The Concept of Calligraphy Learning In Mushthafawiyah Purba Baru Mandailing Natal (Madina) Boarding School - Mulyadi Mulyadi; Jovial Pally Taran (Jurnal Recoms, 2024)
Calligraphy is the art of writing text into a form of painting using a pen, brush, or other writing instrument onto a particular medium. Initially calligraphy was poured onto papyrus paper media, but along with the development of time, calligraphy media were also found in other more varied media such as stones, walls, coins, silk, canvas paper, jewelry, brass plates, glass, ceramics, and others. This research aims to find out the concept of calligraphy learning in Mushthafawiyah Islamic boarding school. The research method used is a qualitative method which includes interviews and data collection from literature sources. Mushthafawiyah Islamic Boarding School Purba Baru Mandailing Natal held its learning process in the classroom and the learning media included a blackboard, khat pen, handam, highlighter and book. The learning material is delivered by means of the teacher providing samples on the blackboard then the santri imitate it.